Personality and Career Preference of Drug Abusers in Sabah - Julianah Saguni; Norzihan Ayub; Puteri Hayati Megat Ahmad; Guan, Teik Ee (2018)
Unemployment issue is becoming a factor which causes relapses especially among former drug addicts that has undergone rehabilitation. Therefore, this paperwork seek to unfold and discuss degree of relationships between introvert and extrovert personality with career interest according to six RIASEC major field to drug addicts. Research objective are to identify the relationship between introvert and extrovert personality with career interest among drug addicts in Sabah. Most of the respondent in treatment center has no knowledge about their own personality in career development especially after finishing treatment thus causing relapse due to failure of getting the right employment for themselves. It is considered serious due to economic and life instability are one of the factor which contribute to relapse among drug addicts. Occupation or career selection are constantly highlighted as one of the major problem in former drug addict life. This shows that a careful career selection needs to be done.Career process are also continuous process of involvement to help self-development especially in line of job they do. Therefore, it is hopeful that this research could give valuable impact and use to drug addicts rehabilitation authority with implementation of career guidance to clients hence assisting them in making effective career choice in the future.